EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The articles in this issue deal with several different themes. What brings them together is their diligent attempt to grapple with the complex realities of today’s world of teaching, values and beliefs. While each author addresses a specific content area, he or she also locates the content area within the broader context of quality education, curriculum, social theory and design. Each article provides some important insight into an area of the educational field.